Embodied Human-Computer Interaction in Vocal Music Performance - Baumann, Franziska (Cham : Springer International Publishing : Imprint: Springer, 2023)
This SpringerBrief provides a unique insight into the practice and research of the connections between voice, HCI and embodiment. Specifically, it explores how the voice can be embodied and mediated by means of gestural communication through sensor interfaces and aims to situate and contextualise various aspects that generate meaningful connections in such interactive interface performance. The author offers an approach for understanding creative practices between humans and computers in gestural live music performance, from the perspective of the embodied relationships created within such systems. Underlying practices, principles and sensor technologies that support creativity in embodied human-computer interaction in vocal music performance are examined and a dynamic framework and tools for anyone wishing to engage with this subject in depth are presented. The book is essential reading not only for musicians, composers, researchers, application developers,musicologists and educators but also for students and tertiary institutions as well as actors and dramaturgs in a music context. .
Introduction -- The embodied voice -- The mediated voice -- Embodied interface performance with gestural systems.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Performing arts; Theater; Virtual reality; Augmented reality; User Interfaces and Human Computer Interaction; Theatre and Performance Arts; Virtual and Augmented Reality